Experimental Study on the Working Fluid Filling Rates of Microchannel Evaporator in a Special Separate Type Heat Pipe - Hu Zhangbao; Zhang Zhiwei; Jin Tingxiang; Shao Shuangquan; Zhang Hainan (Zhileng xuebao)
The microchannel heat exchanger was used as the evaporator of a separated type heat pipe, and the working fluid filling rate of the separate type heat pipe was studied experimentally when the filling rate changed from 80% to 150%. The heat transfer, the wall temperature of microchannel evaporator and the EER of the system were measured. The heat transfer characteristics under different filling rate were analyzed respectively, and the heat transfer coefficient was calculated. The results show that the heat transfer increased with the temperature difference between the indoor air and the outdoor air. The optimal filling rate was about 120%. Moreover, the microchannel evaporator was compared experimentally with the finned tube evaporator under the condition of same heat transfer. The weight and the refrigerant charge of the microchannel evaporator is 45% and 15.9% lower than that of the finned tube evaporator, respectively. The EER of the system with the microchannel evaporator is 2.8% higher than that of the system with the finned tube evaporator.